Book Review: Lake Tourism: an Integrated Approach to Lacustrine Tourism Systems. (4th June 2007) - Hall, Derek
Lake Tourism: an Integrated Approach to Lacustrine Tourism Systems, edited by Michael C. Hall and Tuija Harkonen. Clevedon, UK: Channel View Publications, 2006. 256pp. Hardback ISBN 1-84541-041-6; Paperback ISBN 1-84541-040-8; E-book ISBN 1-84541-042-4